Implementation of a hybrid mathematics module to minimize students’ learning obstacles when interpreting fractions - Isnawan, Muhamad Galang; Belbase, Shashidhar; Yanuarto, Wanda Nugroho (International Journal of Didactic Mathematics in Distance Education, 2024)
The COVID-19 pandemic forced a sudden shift to emergency remote teaching—commonly referred to as panic-gogy—which exacerbated students’ learning challenges, particularly in mathematics. This study addresses the urgent need for responsive instructional designs by integrating parental insights into the learning process. Framed within the didactical design research (DDR) methodology, this study aimed to develop an alternative learning approach to reduce obstacles in students’ understanding of fractions during panic-gogy. Participants included 56 junior high school students (aged 13–18) and 71 parents (aged 35–50) from a school in Indonesia. Data were collected using a fraction concept test, semi-structured interviews, a hybrid mathematics module, and documentation analysis. Thematic qualitative analysis was conducted with the aid of NVivo 12. Results revealed that students struggled with interpreting the meaning of fractions, often due to inadequate teacher explanations. Parental feedback emphasized a strong preference for face-to-face instruction, even when delivered via online platforms. The hybrid mathematics module, designed in response to these findings, successfully integrated contextual problem situations to support the construction of fractional meaning and reduce learning barriers. This study contributes to the body of knowledge by highlighting the value of involving parents in instructional design and demonstrating how hybrid modules can mediate learning in crisis contexts. The findings have implications for developing resilient educational strategies in future disruptions.